Spatial quantitation of FISH signals in diploid versus aneuploid nuclei. Issue 4 (17th December 2013) - Shete, Amol; Rao, Pulivarthi; Pati, Debananda; Merchant, Fatima
Abstract Fluorescence in situ hybridization (FISH) is the most widely used molecular technique to visualize chromosomal abnormalities. Here, we describe a novel 3D modeling approach to allow precise shape estimation and localization of FISH signals in the nucleus of human embryonic stem cells (hES) undergoing progressive but defined aneuploidy. The hES cell line WA09 acquires an extra copy of chromosome 12 in culture with increasing passages. Both diploid and aneuploid nuclei were analyzed to quantitate the differences in the localization of centromeric FISH signals for chromosome 12 as it transitions from euploidy to aneuploidy. We employed superquadric modeling primitives coupled with principal component analysis to determine the 3D position of FISH signals within the nucleus. A novel aspect of our modeling approach is that it allows comparison of FISH signals across multiple cells by normalizing the position of the centromeric signals relative to a reference landmark in oriented nuclei. Using this model we present evidence of changes in the relative positioning of centromeres in trisomy‐12 cells when compared with diploid cells from the same population. Our analysis also suggests a significant change in the spatial distribution of at least one of the FISH signals in the aneuploid chromosome complements implicating that an overall change in centromere position may occur in trisomy‐12 due to the addition of an extra chromosome. These studies underscore the unique utility of our modeling algorithms in quantifying FISH signals in three dimensions. © 2013 International Society for Advancement of Cytometry